Homilias no pontificado de Francisco: análise das homilias da Semana de Oração pela unidade dos Cristãos (2014-2020) - Silva, Luiz Gustavo Uchoa da (2022)
This research project aims to reflect on the relevance of homilies in the context of the new evangelization. For this purpose, it is based on the pontificate of Francisco the reflection on how important are well-prepared homilies, endowed with parresia, capable of generating conversion and commitment. In this sense, in Francisco, it is possible to see a materialized ideal, in other words, translated words in life by authentically evangelical attitudes. Therefore, this man of God can be taken as a great reference because of his dialogue targets, mercy and meeting that bring him closer to everyone, with no reservation, especially of the poorest. In fact, without fear of rash judgments that would try to stop him, Francisco proclaims the Gospel with truth, without giving in to flattery or rhetoric. Furthermore, in a time marked by different ways of sectarianism, the current pontiff becomes an icon of communion. As a result, its ecumenical praxis deserves to be highlighted as a model to be followed in our times. Namely, the ecumenical perspective in the Francisco’s Pontificate is the result, firstly, of the ecclesiological conception of the Second Vatican Council. However, it is also something that is thanks to the testament received from those Popes who succeeded him, especially Saint John XXIII. Understanding the Church as a place of dialogue, encounter and communion – key words of this pontificate – is presumable thanks to the life history of Jorge Mario Bergoglio, who as has been said, is the son of the Council. Different from Montini (Paulo VI), Wojtyla (João Paulo II) and Ratzinger (Bento XVI), who helped to manager the Council, Bergoglio was a recipient of the same. As such, Francisco seeks to communicate to his followers the principles of the Council (such as ecumenical, interreligious and worldwide). Thus, the analysis of his annual homilies, at the time of the Week of Prayer for Christian Unity, reveals his conception of ecumenism in a pragmatic scope, that is, as a communion lived by Christians of different traditions who can unite in search of social promotion, common good, justice and peace